Scrutinizing the myth of kumunity: the semiotics of the philippines’ pinoy big brother season 10 - Rosario Ancheta, Jeffrey; Aguilar Villena, Joseph (Penerbit Universiti Kebangsaan Malaysia, 2024)
In applying Roland Barthes' semiotic theory to the analysis of Pinoy Big Brother Season 10 (Dyogi, Katigbak, Vidanes & Andrada, 2021-2022), this study delves into the intricate layers of meaning embedded in the show's 'Kumunity' concept, a term created by the fusion of 'Kumu,' a social media entertainment app, and "community." The primary focus is on unraveling the myth that the 'kumunity' symbolizes within the broader context of the reality television landscape in the Philippines. The investigation meticulously scrutinized selected components of the show—images, music, and dialogues—to elucidate the orders of signification, exposing the nuanced and multifaceted meanings conveyed. The 'kumunity' is portrayed as mirroring a tangible community with shared goals among housemates, showcasing a cohesive objective reminiscent of a localized collective. However, beneath this surface portrayal, this study uncover a rich tapestry of implicit meanings. These include subtle assertions of authority and power dynamics, the reinforcement of cultural nuances, the elevation and glorification of resilience as a virtue, and instances of disunity within the overarching support system. The study, through extensive analysis, goes beyond the apparent and reveals the intricate web of hidden ideologies within the signs presented in Pinoy Big Brother Season 10. It sheds light on the subtle yet impactful societal messages that permeate the realm of reality television, contributing to a more comprehensive understanding of the show's influence on cultural perceptions and dynamics.